Utilização do software GeoGebra no ensino das funções trigonométricas - Souza, Jakson Idernando Gonzaga de (2014)
Discuss the pedagogical use of technological resources in mathematics classes has been the focus of many studies, since they alone do not guarantee a new educational model. In this sense, this work aims to explore the GeoGebra software as a teaching resource in the teaching of the trigonometric functions for students of 2nd year of high school, a school of private schools in the state of Ceará, through visualization of the trigonometric functions in the unit circle , their graphical representations and the role of parameters in the construction of the graphs of these functions, providing the opportunity for contact with the different features present in the classroom. This work shows that the use of computer simulation can be an effective means of promoting learning significantly, thus facilitating the development of skills in understanding by students of the content related to trigonometric functions, in an environment where the subjects covered are worked using the broad field of information and computer interactions.